The knowledge of medical students, from a medical school in Recife, about immunization (Research, Society and Development, 2020)
Objective: To assess the knowledge of medical students about immunization. Methods: A cross-sectional descriptive study was carried out using a 53-question questionnaire involving the main aspects of the available vaccines. The global assessment considered as unsatisfactory knowledge less than 27 correct questions ( 75%). Results: A total of 351 medical students were analyzed, distributed over all periods of graduation. The students' age range was 17 to 38 years, where 29.9% were male and 70.1% female. In the global assessment, 59.5% had unsatisfactory knowledge, 37.6% satisfactory and only 2.8% as very satisfactory. The use of BCG in HIV patients and the hepatitis B vaccination schedule were answered correctly in 27.6% and 56.1% respectively. Most students (64.7%) responded correctly about the Influenza vaccination during pregnancy, although only 8.3% knew about adverse reactions to DTP. Regarding the HPV vaccine, 72.4% of adequate knowledge about its importance in the prevention of cervical cancer was obtained. When assessed whether meningococcal C vaccine was included in the vaccination schedule, 66.7% responded correctly. There was progression of knowledge with the year of graduation (p